VEGF mitigates histone‐induced pyroptosis in the remote liver injury associated with renal allograft ischemia–reperfusion injury in rats. Issue 8 (23rd March 2018) - Zhao, Hailin; Huang, Han; Alam, Azeem; Chen, Qian; Suen, Ka Chuen; Cui, Jiang; Sun, Qizhe; Ologunde, Rele; Zhang, Wenwen; Lian, Qingquan; Ma, Daqing
Abstract : Clinical evidence has indicated a possible link between renal injury and remote liver injury. We investigated whether extracellular histone mediates remote hepatic damage after renal graft ischemia–reperfusion injury, while vascular endothelial growth factor (VEGF) is protective against remote hepatic injury. In vitro, hepatocyte HepG2 cultures were treated with histone. In vivo, the Brown‐Norway renal graft was stored in 4°C preservation solution for 24 hours and then transplanted into a Lewis rat recipient; blood samples and livers from recipients were harvested 24 hours after surgery. Prolonged cold ischemia in renal grafts enhanced liver injury 24 hours after engraftment. Caspase‐1, ASC, NLRP3, and AIM2 expressions in hepatocyte, CD68 + ‐infiltrating macrophages, tissue, and serum interleukin‐1β and ‐18 were greatly elevated, indicating that pyroptosis occurred in the liver and resulted in acute liver functional impairment. Blocking the caspase‐1 pathway decreased the number of necrotic hepatocytes. VEGF treatment suppressed the hepatocyte pyroptosis and liver function was partially restored. Our data suggested that renal allograft ischemia–reperfusion injury is likely associated with acute liver damage due to hepatocyte pyroptosis induced by histone and such injury may be protected by VEGF administration. VEGF, therefore, may serve as a new strategy against other remote organ injuries related to renal transplantation. Abstract : Vascular endothelial growth factor mitigates pyroptosis in the liver following renal allograft engraftment.